Ecological research in the perspective of using forest in adaptation to climate change in Cameroon (Central Africa) - Sonwa, D.J.; Nkem, J.; Foahom, B.; Nkongmeneck, B.A. (2009)
Understanding the vulnerability of forest and forest related sectors to climate change, mainstreaming the use of forest into adaptation strategies are some of the challenges faced by forestry research, developers and stakeholders. Despite the multiple efforts to mitigate climate change, it is well established that climate change will occurred and will increase the vulnerability of developing countries, particularly the poorest population. This group of population is well reprented in developing countries and depends mainly on rain related activities for their basic subsistence. As they rely on forest resources for their subsistence, looking in these natural resources ways to help them cope with these changes is the challenge of the forest and climate change managers. For the research communities of the developing countries, it not always evident on how to shift from the existing ecological research framework to the new one in which they assess vulnerability of forest but also their use in the adaptation to climate change. The current presentation in the context of Cameroon highlighted (1) the impact of climate change in forestry related sectors, (2) The current ecological research infrastructure, (3) what is needed to properly integrate forest resources uses in adaptation plan and thus enable the proper use of forest resources to adapt to climate change.